MINORITY CRISIS IN CAMEROON.THE CASE OF THE PYGMY TRIBE. - MARIE ORANG AYUK (Graduate School of International Studies Ajou University, 2018)
ABSTRACT The concept of marginalization of indigenous people ‘the pygmy’ tribe faces great threat from the society and nations they belong for they are mal-treated. This project is to examines the situation of the Baka indigenous people <THE PYGMY> in Cameroon from ancestral and customary right perspective. The Baka people are located in the eastern southern region of Cameroon in the rainforest area. The lives of the baka pygmy are Constance under threat from poachers. The way of living in the forest seem to people out of the forest to be primitive though infact is extra-ordinary to the pygmies because all the resources they need for their life is around them. Their health situation is alarming due to lack of good healthcare centers, they believe in traditional medicines which remain the first aid call for many Baka overwhelming in sorcery and witchcraft which often create a fatalist altitude that stop them from seeking proper medical treatment and sticking to drugs. They are political negligible, their tradition is damage and their destiny uncertain. The face impartiality and marginalization due to their dwarf origin and fight to get daily needs such as food, medical care, education. This project shows the condition and also enlists the Human Rights violation. It give a deep explanation of how the rights of the pygmy are violated and their ancestral land expropratited due to preservation of the environment .A detail analysis of the impact that Chad-Cameroon oil pipeline project on the Baka pygmy show that they have been evidences’ of negative consequences in the political, Economic and Socio-cultural domain. Some proposed solutions have been advanced has a remedy to the above elaborated problem. Most of the solutions will genuinely fall on the side of the government by creating a level praying ground for all stakeholders to come on board for a better tomorrow for the pygmy.
학위논문(석사)--Graduate School of International Studies Ajou University :NGO학과,2018. 8
Keywords: IDC